OUTCOMES OF PATIENTS UNDERGOING PERCUTANEOUS CORONARY INTERVENTION WITH CHRONIC TOTAL OCCLUSIONS - UDDIN , I; SHIREEN, Dr; GHAFFAR , S; MALIK, Z; HASHMI , MO; JAMIL, W (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to assess the efficacy of percutaneous coronary intervention (PCI) with chronic total occlusions (CTO) in a cardiology department in Peshawar, Pakistan, between January 2021 and December 2022. The study included 190 to 200 patients, most of whom had a history of hypertension and diabetes and were predominantly male. The successful CTO-PCI group had significantly lower major adverse cardiac events (MACE) and target vessel revascularization (TVR) rates than the failed CTO-PCI group. Younger age, male gender, absence of previous myocardial infarction, and lower J-CTO score were significant risk factors for CTO PCI success. Long-term outcomes indicated that CTO PCI was linked to lower rates of MACE, TVR, and repeat revascularization compared to non-CTO PCI. These results indicate that CTO-PCI can be a safe and efficient treatment option for patients with chronic total occlusions. Identification of significant risk factors can aid in selecting patients who are likely to benefit from this procedure. Further research is required to confirm these findings and examine the long-term outcomes of CTO-PCI in larger patient cohorts.